Common Variation in SIM1 Is Reproducibly Associated With BMI in Pi ma Indians - Traurig, Michael (American Diabetes Association, 2009)
OBJECTIVE: Haploinsufficiency of SIM1 is a cause of rare monogenic obesity. To assess the role of SIM1 in polygenic obesity, this gene was analyzed in the Pima Indian population, which has a high prevalence of obesity. RESEARCH DESIGN AND METHODS: SIM1 was sequenced in 96 individuals. Variants (n = 46) were genotyped in a population-based sample of 3,250 full-heritage Pima Indians and in a separate replication sample of 2,944 predominately non–full-heritage subjects from the same community. RESULTS: Variants spanning the upstream region of SIM1 through intron 8 were associated with BMI in the full-heritage Pima Indians, where the strongest associations (P ∼ 10(−4) to 10(−6)) were with common variants (risk allele frequency 0.61–0.67). The difference in mean BMI between individuals homozygous for the major allele compared with homozygotes for the minor allele was ∼2.2 kg/m(2) (P = 2 × 10(−5) for rs3213541). These associations replicated in the separate sample of subjects from the same community (P = 5 × 10(−3) for rs3213541). The strongest associations (P = 4 × 10(−7), controlled for age, sex, birth year, and heritage) were seen in the combined sample (n = 6,194). The risk allele for obesity was more common in full-heritage Pimas than in the mixed-heritage subjects. Two variants (rs3734353 and rs3213541) were also genotyped in 1,275 severely obese and 1,395 lean control subjects of French European ancestry. The Pima risk alleles were the minor alleles in the European samples, and these variants did not display any significant association (P > 0.05). CONCLUSIONS: Common variation in SIM1 is associated with BMI on a population level in Pima Indians where the risk allele is the major allele.